2001
DOI: 10.15506/jog.2001.27.7.385
|View full text |Cite
|
Sign up to set email alerts
|

New gemstone occurrences in the south-west of Madagascar

Abstract: In late 1998, spectacular gemstone occurrences were discovered in the south-western part of Madagascar. The secondary deposits extend from the south of the Isalo National Park near the town of Ranohira up to the town of Sakahara further west with major mining areas around Ilakaka and south of Ankazoabo. The occurrences produce pink, blue, violet, yellow, orange, green, pale brown and colourless corundum varieties, spinels, chrysoberyls, garnets, aquamarines, tourmalines and other gems. Of particular importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Alexandrite originating from phlogopite-bearing host rocks comes from primary emerald deposits in the Mananjary region of Madagascar (Schmetzer and Malsy, 2011a). The other deposit, in the Ilakaka region (Hänni, 1999;Milisenda et al, 2001), is a secondary deposit where different varieties of chrysoberyl-including alexandrite-have been found. Occasionally, large alexandrite crystals of gem quality have been recovered in the Lake Alaotra region.…”
Section: Alexandrite Geographic Localities: a Brief Summarymentioning
confidence: 99%
“…Alexandrite originating from phlogopite-bearing host rocks comes from primary emerald deposits in the Mananjary region of Madagascar (Schmetzer and Malsy, 2011a). The other deposit, in the Ilakaka region (Hänni, 1999;Milisenda et al, 2001), is a secondary deposit where different varieties of chrysoberyl-including alexandrite-have been found. Occasionally, large alexandrite crystals of gem quality have been recovered in the Lake Alaotra region.…”
Section: Alexandrite Geographic Localities: a Brief Summarymentioning
confidence: 99%
“…In the cutting and sorting processes in Thailand, material from Tunduru is commonly mixed with imported rough from Ilakaka, Madagascar. However, at the time of writing (March 2007) gems of the taaffeite group have neither been reported from Ilakaka (see, for example, Schmetzer, 2000;Milisenda et al, 2001) nor identified in the laboratory of the Institut de Gemmologie de Madagascar in Antananarivo (T. Ramerison, pers. comm., 2006).…”
Section: Methodsmentioning
confidence: 99%
“…UV-Vis-NIR absorption spectra of all samples were similar to other magmatic-related origin sapphires. The examination revealed Fe 3+ -related peak at 380-390 nm and 450 nm, [3,15,16] while absorption band due to Fe 2+ −Ti 4+ IVCT displayed between 500 and 800 nm [9,[15][16][17][18] and strong broad absorption band toward the near-infrared region, which thought to be related to Fe 2+ −Fe 3+ IVCT, [3,9] possibly with the involvement of Fe 2+ -Fe 3+ -Ti 4+ clusters. [7,15,[19][20][21] However, Na-Phattalung et al(2018) [8] proposed that the absorption of Fe 2+ −Ti 4+ IVCT from the simulation should present at 623 and 912 nm, which the former was not apparent in this study and the latter could be superimposed by the strong broad absorption band toward near-infrared region (Fig-…”
Section: Uv-vis-nir Absorption Spectroscopymentioning
confidence: 99%